2019
DOI: 10.1111/jcmm.14393
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract protects human melanocytes from H2O2‐induced oxidative stress by activating Nrf2

Abstract: Vitiligo is a common skin depigmenting disorder characterized by the loss of functional melanocytes. Its pathogenesis is complicated and oxidative stress plays a critical role in the development of vitiligo. Thus, antioxidant therapy is a promising therapeutic strategy to prevent or even reverse the progression of depigmentation. Ginkgo biloba extract EGb761 has been confirmed to have protective effects on neurons against oxidative stress. Notably, several clinical trials have shown that patients with stable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Furthermore, we found that knockdown of Nrf2 by Nrf2-siRNA transfection markedly diminished the curcumin-induced up-regulation of Nrf2, HO-1 and NQO1. Similarly, a previous study has found that knockdown of Nrf2 could decrease the expression level of HO-1 and NQO1 [56]. Here, we have shown that knockdown of Nrf2 decreased the protective effect of curcumin pre-treatment on the cell viability against oxidative stress, suggesting that Nrf2 is a key factor in maintaining the survival of HTR8/SVneo cells.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, we found that knockdown of Nrf2 by Nrf2-siRNA transfection markedly diminished the curcumin-induced up-regulation of Nrf2, HO-1 and NQO1. Similarly, a previous study has found that knockdown of Nrf2 could decrease the expression level of HO-1 and NQO1 [56]. Here, we have shown that knockdown of Nrf2 decreased the protective effect of curcumin pre-treatment on the cell viability against oxidative stress, suggesting that Nrf2 is a key factor in maintaining the survival of HTR8/SVneo cells.…”
Section: Discussionsupporting
confidence: 81%
“…Polyphenols are preferred owing to their antioxidant activities. Polyphenols compounds including Ginkgo biloba extracts, apigenin and baicalin have all been documented in vitro to activate the Nrf2 pathway to counteract oxidative stress as yet 61,94,95 . Quercetin also possesses anti‐inflammatory and antioxidative capacity, albeit not studied in vitiligo treatment 96 .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Besides, in the ABTS, DPPH, and FRAP assays, the MSI has stronger free radical scavenging power and reduction capacity than the ASI. In addition, the extracts of natural products effectively inhibit cell damage by suppressing oxidative stress [21][22][23], and the Nrf2/HO-1 signaling pathway plays an important role in mitigating oxidative stress damage to cells and tissues [24], and HO-1 is one of the important endogenous protective enzymes of downstream of the Nrf2/HO-1 pathway [25], and the expression of HO-1 can inhibit oxidative reactions and thus protect cells and tissues from free radical damage [26]; the modern research had shown that natural product extracts are effective against H 2 O 2 -induced 5 BioMed Research International oxidative stress by activating Nrf2/HO-1 pathway [27,28]. In this study, MSI effectively reduced ROS generation in cardiomyocytes, demonstrating its oxidative stress suppressing action, and the expression of the regulatory genes (Nfe212, Hmox-1, and Nqo1) has increased significantly after H 2 O 2induced H9c2 cells pretreated with MSI; furthermore, the expression levels of Gclm, Gclc, and Gst mRNA have elevated.…”
Section: Discussionmentioning
confidence: 99%